Clinical profile of hospitalized HIV-infected children in Bangladesh, a low-HIV-prevalence country. (May 2014) - Shahrin, Lubaba; Leung, Daniel T.; Matin, Nashaba; Kawser, Chowdhury Ali; Pervez, Mohammed Moshtaq; Chisti, Mohammod Jobayer
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Bangladesh has a low HIV prevalence and data on the risk factors and clinical presentation of HIV-infected children are lacking. Objective: To describe the clinical characteristics of hospitalized HIV-infected children in Bangladesh and determine the factors associated with a low CD4 count. Methods: An anonymous, retrospective review was undertaken of the medical records of all patients admitted to the HIV unit of the iccdr, b Dhaka Hospital between February 2009 and July 2012. Demographic, clinical and laboratory data were extracted from the electronic medical record system. HIV-infected children with a low absolute CD4 count (<200 cells/μl) were compared with HIV-infected children with a CD4 count ≧200 cells/μl. Results: Of 266 HIV-infected patients, 24 were children (9%), 13 (54%) of whom were male. Ages ranged from 2 to 17 years (median 7). Of the 21 (88%) children who acquired the infection by vertical transmission, median age at diagnosis was 5·2 years, and the parents of 19 (79%) reported a history of external migration. Children commonly presented with prolonged fever (n = 14, 58%), recurrent cough (n = 14, 58%), failure to thrive (n = 11, 46%) and recurrent diarrhoea (n = 4, 17%). Six (25%) patients had tuberculosis, four (16·7%) had herpes zoster and four (16·7%) were diagnosed with Pneumocystis jirovecii pneumonia. One child died during hospitalization. Children with a low CD4 count (<200 cells/μl) more often had severe wasting (95% CI 1·2–453·97) and severe under-nutrition (95% CI 1·39–196·25) than those with a higher CD4 count*. Conclusion: The majority of HIV-infected children presenting to an inpatient speciality ward in Dhaka acquired HIV through vertical transmission, and most of the parents had a history of external migration. Further studies are needed to determine the optimal strategy for preventing mother-to-child transmission and for early identification and treatment of HIV-infected children in this low-prevalence country.